The Role of Sharia Accounting in Strengthening Indonesia’s Halal Industry Ecosystem - Prasetyo, Aji; Sri Guntur, Yohanes; Khayati, Ismatul (El-Qist: Journal of Islamic Economics and Business (JIEB), 2025)
The global halal industry continues to experience robust growth, yet a critical dimension remains underexplored: the integration of Sharia-compliant financial management within halal-certified enterprises. While most regulatory and scholarly attention has been directed toward ensuring product halalness, the financial practices of halal industry players are often misaligned with Sharia accounting principles. This study investigates the role of Sharia accounting in strengthening the integrity and sustainability of Indonesia's halal industry, using a phenomenological qualitative approach based on in-depth interviews with key stakeholders in East Java. Grounded in the maqāṣid al-sharī‘ah framework, particularly the protection of wealth (hifẓ al-māl), the findings reveal a systemic gap between product-based halal certification and Sharia-compliant financial reporting. The absence of regulatory enforcement, institutional clarity, and professional support has led to fragmented practices, particularly among micro, small, and medium-sized enterprises (MSMEs). This study offers a strategic recommendation to involve Sharia-compliant Public Accounting Firms (PAFs) in assisting halal businesses with financial reporting following Sharia Financial Accounting Standards (SFAS). The novelty of this research lies in highlighting financial governance as an essential yet overlooked pillar of halal assurance—advancing the discourse on halal ecosystem integrity from a global Islamic accounting perspective. For future research, comparative cross-country studies are recommended to examine the implementation and regulatory integration of Sharia accounting within halal industries in diverse legal and institutional settings, particularly between emerging Muslim-majority economies and established halal hubs such as Malaysia, the GCC, and Southeast Asia.